The Effects of Coarse Corn Inclusion in Broiler Diets on Pellet Quality - Aundria M. Ogles; Caitlin E. Evans; Haley K. Wecker; Courtney N. Truelock; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Previous research has demonstrated the benefits of including large grain particle size in poultry diets on gizzard and gastrointestinal tract development. However, including these larger particles may decrease pellet integrity. Therefore, the objective of this study was to evaluate the effect of coarse corn inclusion level on pellet quality. A corn soybean meal-based finisher broiler diet with 1.5% mixer added fat was used in this experiment. Treatments were created by replacing 600 μm corn with 1,200 μm coarse rolled corn at 0, 10, 20, or 30% of the diet. Mash treatments were pelleted using a 30-horsepower pellet mill (Model 1012-2 HD, California Pellet Mill) equipped with a 3/16 × 1 ¼ in. die. Pelleting order was randomized within each replicate with 3 replicates per treatment. Target conditioning temperature was 185°F for 30 s retention time at a 34 lb/min production rate. Samples were analyzed for hot pellet temperature (HPT), fine to pellet ratio (%fines) and pellet durability index (PDI) using the standard tumble box (STD) and Holmen NHP100 (NHP) for 60 s. Data were analyzed using the GLIMMIX procedure of SAS. There were no differences among analyzed variables as the inclusion level of coarse corn was increased (P>0.05). The %fines and PDI remained similar across treatments, regardless of method. In conclusion, increasing the concentration of coarse corn from 0 to 30% did not influence PDI.
Keywords: Pellet quality; coarse corn; particle size; pelleting; poultry; broilers